Telemental Health Use in the COVID-19 Pandemic: A Scoping Review and Evidence Gap Mapping - Abraham, Amit; Jithesh, Anupama; Doraiswamy, Sathyanarayanan; Al-Khawaga, Nasser; Mamtani, Ravinder; Cheema, Sohaila (Frontiers in Psychiatry, 2021)
1.1 Background The COVID-19 pandemic has highlighted telemedicine use for mental illness (telemental health). 1.2 Objective In the scoping review, we describe the scope and domains of telemental health during the COVID-19 pandemic from the published literature and discuss associated challenges. 1.3 Methods PubMed, EMBASE, and the World Health Organization’s Global COVID-19 Database were searched up to August 23, 2020 with no restrictions on study design, language, or geographical, following an a priori protocol (https://osf.io/4dxms/). Data were synthesized using descriptive statistics from the peer-reviewed literature and the National Quality Forum’s (NQF) framework for telemental health. Sentiment analysis was also used to gauge patient and healthcare provider opinion towards telemental health. 1.4 Results After screening, we identified 196 articles, predominantly from high-income countries (36.22%). Most articles were classified as commentaries (51.53%) and discussed telemental health from a management standpoint (86.22%). Conditions commonly treated with telemental health were depression, anxiety, and eating disorders. Where data were available, most articles described telemental health in a home-based setting (use of telemental health at home by patients). Overall sentiment was neutral-to-positive for the individual domains of the NQF framework. 1.5 Conclusions Our findings suggest that there was a marked growth in the uptake of telemental health during the pandemic and that telemental health is effective, safe, and will remain in use for the foreseeable future. However, more needs to be done to better understand these findings. Greater investment into human and financial resources, and research should be made by governments, global funding agencies, academia, and other stakeholders, especially in low- and middle- income countries. Uniform guidelines for licensing and credentialing, payment and insurance, and standards of care need to be developed to ensure safe and optimal telemental health delivery. Telemental health education should be incorporated into health professions curricula globally. With rapidly advancing technology and increasing acceptance of interactive online platforms amongst patients and healthcare providers, telemental health can provide sustainable mental healthcare across patient populations.